A prospective observational study of plasma concentrations and safety of combined intravenous lidocaine and epidural ropivacaine in laparotomy surgery - Ottilie Trocheris-Fumery; Alexandre Pruvot; Paul Tarpin; Sophie Collette; Sandra Bodeau; Momar Diouf; Jean-Marc Regimbeau; Hervé Dupont; Stéphane Bar; Youssef Bennis; Osama Abou-Arab (PLoS ONE, 2026)
Intravenous lidocaine (IVL), an alternative to epidural analgesia (EA) for laparotomies, has demonstrated anti-inflammatory and anti-hyperalgesic effects. However, its combination with EA raises concerns about systemic toxicity. This study aimed to assess the safety of this combination in patients undergoing laparotomy. We conducted a prospective observational study at Amiens University Hospital in France, involving adult patients scheduled for laparotomies. Intravenous lidocaine was administered at induction as a 1.5 mg/kg bolus (ideal body weight), followed by a continuous infusion of 2 mg/kg/h maintained until the end of surgery. An epidural catheter was inserted before surgery, prior to induction of general anesthesia, no local anesthetic was administered intraoperatively. Epidural analgesia was initiated at the end of surgery with a 5 mg bolus of ropivacaine, followed by a continuous infusion. The primary outcome was the occurrence of lidocaine and ropivacaine plasma concentrations outside established safety ranges. Lidocaine plasma concentrations were measured 30 minutes after bolus (LP1), at the end of surgery (LP2), and two hours after discontinuation of the infusion (LP3). Ropivacaine concentrations were measured two hours (RP1) and 24 hours after initiation of epidural infusion (RP2). The secondary endpoint the assessment of cardiac and neurological toxicity within 48 hours post-surgery. Fifty patients were included from March 2022 to March 2024. One patient exceeded the lidocaine threshold (LP2), and another exceeded the ropivacaine threshold (RP2). LP1 was 1.8 [1.5–2.4] µg/ml, LP2 was 2.1 [1.6–2.4] µg/ml, and LP3 was 1.2 [0.8–1.7] µg/ml. Ropivacaine plasma concentration was 126 [87–211] µg/L at RP1, and 785 [524–1318] µg/L at RP2. No cardiac or neurological adverse events were observed. The combination of EA and IVL appeared to be safe for major abdominal surgery. Clinical trials Number NCT05368753. EudraCT Number: 2021-005508-37.